New strategy of drinking water sludge as conditioner to enhance waste activated sludge dewaterability: Collaborative disposal. (15th April 2023) - Xiao, Tingting; Wang, Hui; Wang, Xiankai; Wu, Haibin; Yuan, Shijie; Dai, Xiaohu; Dong, Bin
Highlights: DWS and WAS collaborative treatment and disposal was considered and explored. HDWS+O3 enhanced WAS dewaterability with its physical and chemical properties. More Lewis acidic sites on the surface of HDWS meant better catalytic activity. The Al-O bonds were formed and undergo electron transfer for producing more ·OH. EPS structure was damaged by ·OH, resulting in PN unwind and moisture released. Abstract: Drinking water sludge (DWS) and waste activated sludge (WAS) are usually treated separately. With the continuous deepening understanding of the characteristics of two types sludge, the research and application of the collaborative disposal is worth considering. The heated modification DWS (HDWS) rich in inorganic matter and aluminum (Al2 O3 ) can be used as a conditioner to enhance WAS dewaterability using its properties with physical skeleton and chemically catalyzed ozone (O3 ). The results showed that the minimum values of capillary water time (CST) and specific resistance filtration (SRF) for WAS were 20.9±2.40 s and 1.07±0.19×10 13 m/kg at pH=4, O3 dosage=60 mg/g VS and HDWS dosage=700 mg/g VS, corresponding to the reduction of sludge cake water content (Wc) to 60.37±0.97 %. The mechanism of HDWS+O3 enhanced WAS dewaterability was systematically elucidated through pyridine-infrared analysis and density functional theory (DFT) calculations. The surface of Al2 O3 in HDWS had more Lewis acidic sites, and the oxygen atoms of O3 combined with Al atoms to form Al-O bonds and undergo electron transfer, while O3 molecules dissociated to produce more hydroxyl radicals (·OH). With the oxidation of ·OH, the extra-microcolony/cellular polymers (EMPS/ECPS) structure were destroyed and became looser, promoting the conversion of internal moisture to free moisture. Zeta potential tended to zero, particle size increased, and the surface was more hydrophobic. Correlation analysis revealed that the component content, protein (PN) secondary structure and molecular weight (MW) in ECPS were positively and more strongly correlated with the sludge dewaterability compared to EMPS. The discovery of HDWS+O3 applied to effectively enhance WAS dewaterability provided an inspiring perspective on the emerging DWS and WAS co-processing disposition. Graphical abstract: Image, graphical abstract